2022
DOI: 10.3390/jfmk7040082
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of the Reverse Plank Exercise on Muscle Thickness and Postural Angle in Individuals with the Forward Shoulder Posture

Abstract: The forward shoulder posture (FSP) results from shoulders being pulled forward by shortened anterior shoulder girdle muscles. The objective of this study was to investigate the short-term effectiveness of the reverse plank exercise on parascapular muscle thickness and forward shoulder angle (FSA) in patients with FSP. Participants were divided into the FSP and non-FSP (NFSP) groups based on the observed angle between the horizontal line of the C7 spinous process and the acromion process. All participants perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…The other immediate changes related to mobility, displayed as lower flexed lumbar mobility (fLM) and higher sacral mobility (fSM). Researchers have been investigating the immediate effects of exercises with the purpose to understand and find mechanisms that positively influence biophysical aspects of the body for years [ 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 ]. Without treatment, anomalies such as hyperkyphosis, hypolordosis, and mobility deficits can promote pathophysiological processes, leading to musculoskeletal pain conditions (e.g., low back pain) [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The other immediate changes related to mobility, displayed as lower flexed lumbar mobility (fLM) and higher sacral mobility (fSM). Researchers have been investigating the immediate effects of exercises with the purpose to understand and find mechanisms that positively influence biophysical aspects of the body for years [ 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 ]. Without treatment, anomalies such as hyperkyphosis, hypolordosis, and mobility deficits can promote pathophysiological processes, leading to musculoskeletal pain conditions (e.g., low back pain) [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is regarded as problematic for several reasons including the risk of disc degeneration, mobility deficits, and overall reduction in quality of life [ 14 ]. Among conservative treatments analyzing immediate effects, Koo et al (2022) found a positive postural adaptation in patients with forward shoulder posture (characterized by hyperkyphosis), following a five-set reverse plank protocol [ 27 ]. Other strategies with proven immediate corrective effects include taping [ 36 ] and the use of ortheses [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O hundred é exercício abdominal isométrico típico utilizado no método Pilates associado ao padrão respiratório e a movimentação de membros superiores, caracterizado por extensões e flexões de ombros sequenciadas e ritmadas para toda inspiração e expiração [6], no qual esse padrão respiratório repete-se por dez vezes em uma contagem total de cem movimentações dos membros superiores com objetivos de estimular a circulação sanguínea, centro de forças, respiração e a resistência muscular [7]. O plank é um exercício isométrico utilizado para estabilizar o core e a coluna vertebral por meio do fortalecimento dos músculos do tronco, entre eles o MRA [8], podendo ser facilmente modificados usando várias posições para aumentar a exigência de força muscular e em níveis de dificuldade, como o frontal, cotovelo, lateral e reverso [9]. O crunch é um dos exercícios isotônicos mais comuns para recrutamento do MRA, podendo ter variações que exigem mais a porção superior e outras a porção inferior, além de ser simples e prático [5,10].…”
Section: Introductionunclassified